Optimization of WEDM process parameters for machining hybrid composites (LM6/B4C/Fly Ash) - Udaya Prakash, Jayavelu; Sarala Rubi, Charles; Jebarose Juliyana, Sunder; Salunkhe, Sachin; Özerkan, H. B.; Cepova, Lenka (Frontiers in Mechanical Engineering, 2025)
IntroductionWire-electric discharge machining (WEDM) possesses multiple benefits over traditional production approaches; it allows for the precise processing of complex and rigid particulate-reinforced composite materials. Aluminium alloys have found widespread applications in surgical components, shipbuilding, aircraft, automobiles, and inhaling gas cylinders for scuba diving, due to its good strength, and light weight properties.MethodsThe main aim of this investigation is to optimize different process variables for LM6/B4C/Fly ash particle reinforced hybrid composites using WEDM to attain performance metrics such as maximum material removal rate (MRR) and minimal surface roughness (SR). Taguchi’s L27 orthogonal array (OA) matrix and Grey Relational Analysis (GRA) were used.Results and DiscussionAccording to ANOVA, the two variables with the most significant impact on MRR and SR are gap voltage and reinforcement percentage, with respective impacts of 29.59% and 20.69%. When the composite is machined, the following process variables work best: GV of 30 V, Ton of 10 µs, Toff of 2 µs, WF of 4 m/min, and R of 6%. A low gap voltage causes the erosion to rise and the MRR to increase. However, SR will also increase which is undesirable, so optimum gap voltage values are required for WEDM.